2010
DOI: 10.3109/02770900903519908
|View full text |Cite
|
Sign up to set email alerts
|

Asthma Knowledge and Asthma Management Behavior in Urban Elementary School Teachers

Abstract: BACKGROUND While schools are an important setting for asthma care in youth, teachers’ asthma knowledge and symptom management is poor. This study investigated the knowledge, prevention and management behaviors, and communication regarding asthma of teachers of low income ethnic minority students. It was hypothesized that relative to colleagues whose students did not have active asthma (i.e., did not have symptoms during the day), teachers of students with active asthma would have better asthma knowledge and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
61
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 28 publications
(32 reference statements)
5
61
4
Order By: Relevance
“…These results differed from another study that reported the most common treatment was for teachers to send students to the nurse (without specifying the need for medication) (17). The aforementioned study did not differentiate between PE teachers and classroom teachers.…”
Section: Discussioncontrasting
confidence: 97%
See 2 more Smart Citations
“…These results differed from another study that reported the most common treatment was for teachers to send students to the nurse (without specifying the need for medication) (17). The aforementioned study did not differentiate between PE teachers and classroom teachers.…”
Section: Discussioncontrasting
confidence: 97%
“…In addition, many teachers incorrectly believed children with asthma should avoid strenuous activity, and that asthma medication taken prior to activity would not help students during exercise (17). These results, while obtained by surveying school staff, resonate with our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One explanation of this finding is that teachers were not familiar with typical symptoms of an asthma exacerbation, which is consistent with other studies. [22–24] Several teachers admitted to not being comfortable identifying symptoms of an asthma attack. This finding is of concern as teachers who are not able to identify symptoms of acute asthma will likely not be able to effectively assist children who are experiencing an acute exacerbation.…”
Section: Discussionmentioning
confidence: 99%
“…This interpretation is supported by the finding that participant’s as-needed reliever medication is refilled at higher rates than daily controller medication (26), and the fact that early adolescents are often not adherent to treatment regimens (13). This reactive management style is not unique to early adolescents; it has also been found to be used by parents (27, 28) as well as elementary school teachers (29), suggesting that early adolescents may learn to manage asthma reactively through modeling.…”
Section: Discussionmentioning
confidence: 99%